2000
DOI: 10.1111/1467-7687.00140
|View full text |Cite
|
Sign up to set email alerts
|

Motor memory is a factor in infant perseverative errors

Abstract: Why do infants make perseverative errors when reaching for two identical targets? From a dynamic systems perspective, perseverative errors emerge from repetitive perceptual ±motor activity in novel andaor difficult contexts. To evaluate this account, we studied 9-month-old infants performing two tasks in which they repetitively reached toward either a single target or two identical targets. Results showed that, in the context of the two identical targets, perseverative responses were preceded by the creation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
1
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 62 publications
2
66
1
1
Order By: Relevance
“…Previous work by Thelen and colleagues (2001) demonstrated that a dynamic field model of reaching behavior could capture infants' A-not-B performance. According to Thelen et al, infants' reaches in this task depend on the interaction between a long-term memory of past reaches to the A location and a memory of the cuing event at the B location (see also Diedrich, Highlands, Thelen & Smith, 2001;Diedrich, Thelen, Smith & Corbetta, 2000;Smith, Thelen, Titzer & McLin, 1999). Infants "fail" in this task because the memory of B is not robust and is dominated by the long-term memory of A; infants succeed in this task when they can effectively sustain the memory of B during short-term delays.…”
Section: Piaget's A-not-b Task In Infancymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work by Thelen and colleagues (2001) demonstrated that a dynamic field model of reaching behavior could capture infants' A-not-B performance. According to Thelen et al, infants' reaches in this task depend on the interaction between a long-term memory of past reaches to the A location and a memory of the cuing event at the B location (see also Diedrich, Highlands, Thelen & Smith, 2001;Diedrich, Thelen, Smith & Corbetta, 2000;Smith, Thelen, Titzer & McLin, 1999). Infants "fail" in this task because the memory of B is not robust and is dominated by the long-term memory of A; infants succeed in this task when they can effectively sustain the memory of B during short-term delays.…”
Section: Piaget's A-not-b Task In Infancymentioning
confidence: 99%
“…Although this model effectively captured a host of data and generated novel predictions (e.g., Clearfield, Smith, Diedrich & Thelen, 2006;Diedrich, Clearfield, Smith & Thelen, 2007;Diedrich, et al, 2001;Diedrich, et al, 2000), it is limited in several respects. For instance, it does not address issues of how reference frames are calibrated and re-aligned during the task.…”
Section: Piaget's A-not-b Task In Infancymentioning
confidence: 99%
“…Some researchers suggest that the crucial factor leading to search errors at the B location is not a history of reaching to the A location, but rather a history of attending to or planning to reach to the A location (e.g., Diedrich et al, 2000;Munakata, 1998;Ruffman & Langman, 2002). A number of lines of research have shown performance on the A-not-B task to relate to infant attention.…”
mentioning
confidence: 99%
“…For Mareschal, this is an important 'crack in the story' because reaching is discrete (but cf. Diedrich et al, 1997), whereas my model produces only graded responses. For Smith & Scheier, the reaching process, and bodily movements in general, are critical because they clearly influence subsequent behavior.…”
Section: Fundamental Challengesmentioning
confidence: 70%
“…However, as I argued in the original paper, the data are mixed on this issue; Wellman, Cross, and Bartsch's (1986) meta-analysis did not show any effects of number of A trials, but subsequent studies have demonstrated clear effects of the number of reaches to A (Smith, McLin, Titzer, & Thelen, 1995;Diedrich, Thelen, Smith, & Corbetta, 1997). In addition, Bremner points out that equivocal data on the effects of distinct covers can be understood in terms of the effects of the number of A trials, and that his own work with distinct covers demonstrates effects of the number of A trials.…”
Section: Number Of a Trialsmentioning
confidence: 99%